Multiple myeloma: New surface antigens for the characterization of plasma cells in the era of novel agents - Muccio, Vittorio Emanuele; Saraci, Elona; Gilestro, Milena; Gattei, Valter; Zucchetto, Antonella; Astolfi, Monica; Ruggeri, Marina; Marzanati, Eleonora; Passera, Roberto; Palumbo, Antonio; Boccadoro, Mario; Omedè, Paola (Cytometry. Part B, Clinical cytometry, 2016)
ABSTRACT Background Multiple Myeloma (MM) is a neoplastic disorder characterized by clonal proliferation of malignant plasma cells (PCs). Flow cytometry is an essential tool to confirm diagnosis and evaluate minimal residual disease (MRD). This study aims at identifying new surface PC markers suitable for targeted therapy in MM and able to improve MRD detection. Methods The expression of 82 molecules provided by the “Ninth International Workshop on Leukocyte Antigens” was analyzed by flow cytometry in 5 MM cell lines and in 20 newly diagnosed MM (NDMM) patients. Based on the antigens expression and monoclonal antibody availability, CD150, CD48, CD229, CD352, CD319, CD272, CD86, CD200 and CD184 were subsequently tested in 24 NDMM, 8 relapsed MM (RMM), 6 plasma cell leukemia (PCL) and 13 healthy subjects. Results CD352 was less frequently expressed on NDMM than on healthy PCs; CD200 was more frequently expressed on NDMM than on RMM and healthy PCs. CD150, CD319, CD229, CD352 Mean Fluorescence Intensity (MFI) was lower in pathological than in healthy samples. The proportion of CD150‐positive samples was lower in NDMM and RMM than in healthy subjects; CD86+ samples were less frequent in NDMM than in healthy subjects; CD200+ samples were more frequent in NDMM than in RMM and healthy subjects. Conclusions CD150, CD86 and CD200 can help to identify malignant PCs; CD272, CD319, CD229, CD48 are highly expressed on all PCs and could be considered for targeted therapy. All these antigens could be added to a routine panel for PCs identification and MRD evaluation. © 2015 International Clinical Cytometry Society